Deformation and failure of semicrystalline polymers under dynamic tensile and biaxial impact loading. (December 2016) - Torres, J.P.; Frontini, P.M.; Machado, M.; Major, Z.
Graphical Abstract: Highlights: Dynamic tensile and biaxial impact loading of HDPE are investigated numerically and experimentally. A thermomechanical constitutive model to predict material dynamic response is proposed. The proposed model aims to achieve a compromise between prediction accuracy and formulation simplicity. The model is able to reproduce the essential features of HDPE deformation under biaxial impact loading. A first attempt at modelling HDPE failure using an element deletion technique was carried out. Abstract: We propose a constitutive model to aid in the engineering design of semicrystalline polymer components that may be subjected to biaxial impact loading. To this end, we investigate the thermomechanical and failure behaviour of high density polyethylene (HDPE) under dynamic loading, both experimentally and analytically. We have carried out dynamic tensile tests at 10 1, 10 2 and 10 3 mm/s displacement rates. Digital image correlation (DIC) and infrared thermography were used to measure full 2D true strain fields and determine specimen temperature rise during tensile testing. The results were used to calibrate the constitutive parameters. To analyse the biaxial impact response, we have carried out falling weight impact (FWI) tests at a 4 m/s impact velocity. We assessed the model prediction capabilities by comparing numerical predictions with experimental results and good agreement was observed. The proposed model, which aims to achieve a compromise between prediction accuracy and formulation simplicity, shows that initial linear elastic response coupled with a temperature-dependent power-law viscoplastic flow element and a non-linear strain-hardening element are sufficient to model biaxial stress scenarios.